Agency, injustice, and the struggle against globalised kleptocracy - Ghazavi, VD (2021)
This thesis offers a political theory of overcoming globalised kleptocracy: the phenomenon whereby governing elites who steal from the collective wealth of their society protect those gains in foreign markets. It argues that a legalistic response to globalised kleptocracy is inadequate because it crowds out moral and political commitments to addressing the underlying structural injustice involved in the cross-border flow of corrupt assets. The traditional conception of political responsibility for structural injustice meanwhile is also too narrow because it does not empower all relevant agents in their own contexts, inside and outside the public sphere, to tackle globalised kleptocracy. The thesis thus reframes responsibility for justice in terms of moral imagination and the ideal of restless freedom – the freedom borne of relating to an unjust world, and thus ourselves, more aptly by contributing to its moral progress. In contexts of structural injustice, such freedom is realised through action: by discovering the injustice, recognising its victims, remaking norms and discourses, and advancing institutional innovation and renewal. On this basis, the thesis makes the case for pluralising the agent of change more widely and deeply. However, in making this move, it recognises that agents who could respond to the injustice of globalised kleptocracy face two dilemmas of paralysis: powerlessness, since their actions can seem futile, and elimination, since responsiveness to injustice might be punished in the market. The thesis thus develops a distinctive approach to structural change via two interconnected moves. The first focuses on the radical potential of small-scale action oriented towards achieving moral coherence between agents’ identities, roles, and projects on the one hand, and an unjust phenomenon on the other. The second recasts globalised kleptocracy as a symptom of wider economic forces which themselves must be transformed, particularly beliefs about value creation and value extraction as they relate to finance. The central challenge of globalised kleptocracy turns out to be a deeper problem of moral economy: ensuring agents internalise the social effects of their economic activity, and collectively build institutions that enable them to do so. Rather than waiting for wholesale system change to end globalised kleptocracy, however, agents can influence the direction of change as part of a wider moral ecology. Such ecologies can degenerate and decay, creating greater injustice and inequality, but they can also propel moral progress in a dynamic and non-linear fashion. Crucially, a moral ecology affords multiple pathways for moral agency, while recognising the way in which one’s individual agency is linked with that of others. Action against globalised kleptocracy and for broader transformation towards radical reciprocity in the economy, then, are mutually reinforcing, generating space for progress on both levels as ideals of justice and equality are incrementally instantiated in the market. By revealing how moral agency could be brought to bear in the inhospitable, self-interested domain of finance, and how this can help curtail the specific harms of globalised kleptocracy, the thesis ultimately claims the market economy could be structurally transformed over time through the pursuit of restless freedom.